PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN PT. TRIPATRA ENGINEERING YOGYAKARTA - Venti Eka Nurani (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine the effect of transformational leadership style on job satisfactionof employees of PT Tripatra Engineering Yogyakarta. To determine the effect of workmotivation on job satisfaction of employees of PT Tripatra Engineering Yogyakarta. Todetermine the effect of the work environment on employee job satisfaction of PT TripatraEngineering Yogyakarta. To determine the effect of transformational leadership style, workmotivation and work environment simultaneously on job satisfaction of employees of PTTripatra Engineering Yogyakarta. The variables of this study are transformational leadershipstyle, work motivation, work environment and job satisfaction. The population in this studywere 50 employees of PT Tripatra Engineering Yogyakarta, and at the same time as a sample.Because the entire population is used as a sample, this study uses the census method. Themethod of data collection uses a questionnaire. The analysis technique used is multiple linearregression with a significance level of 5%. The results of the study obtained a regressionequation Y = 0.239X1 + 0.384X2 + 0.299X3. There is a positive and significant influencebetween transformational leadership on job satisfaction of employees of PT TripatraEngineering Yogyakarta, with a significant level of 0.05. There is a positive and significantinfluence between work motivation on job satisfaction of employees of PT TripatraEngineering Yogyakarta, with a significant level of 0.05. There is a positive and significantinfluence between the work environment on job satisfaction of employees of PT TripatraEngineering Yogyakarta, with a significant level of 0.05. There is a simultaneous influence oftransformational leadership, work motivation and work environment on job satisfaction witha significant level of 0.05. Job satisfaction is influenced by transformational leadershipvariables, work motivation and work environment by 50.5%, while the remaining 45.5% isinfluenced by other factors